Case reportInflammatory cerebral amyloid angiopathy: the overlap of perivascular (PAN-like) with vasculitic (Aβ-related angiitis) form: an autopsy case - Szpak, Grażyna M.; Lewandowska, Eliza; Śliwińska, Anna; Stępień, Tomasz; Tarka, Sylwia; Mendel, Tadeusz; Rafałowska, Janina (Folia Neuropathologica, 2011)
Beside advanced age, cerebral amyloid angiopathy (CAA) and hypertension (HTA) are the two most important risk factors for haemorrhagic stroke. Inflammatory changes of amyloid-laden vessels have been reported only in rare sporadic CAA cases. We present the case of a 78-year-old woman with a history of hypertension, dementia and haemorrhagic stroke of the right frontal lobe 2 years before admission. She was admitted with recurrence of symptoms of transient aphasia and central, right-side facial paresis that occurred an hour before her arrival at the hospital. In the admission unit, she was only slightly confused, with no other neurological deficits. An urgent CT scan revealed a recent haemorrhagic stroke in the left frontal lobe. In an hour her condition suddenly deteriorated. After a generalized seizure she presented with right-side hemiparesis with signs of uncal herniation and remained unconscious. A control CT scan showed a large haemorrhagic expansion that comprised the whole left brain hemisphere with 2 cm midline shift. She died about 10 hours after the onset of symptoms. At autopsy chronic inflammation of the thyroid gland, bronchopneumonia, fibrous and fatty heart degeneration and kidney haemorrhagic infarcts were documented. Amyloid deposition and systemic immune disorders in the inner organs were not demonstrated. In neuropathological examination we diagnosed inflammatory form of CAA with coexistence (the overlap) of two, perivascular and vascular, subtypes of CAA-related inflammation.